Rethinking Genocidal Intent: An Interpretation under the International Law and the Jurisprudence of International Criminal Tribunals - Md. Hasnath Kabir Fahim (APPTHI, 2022)
Many criminal lawyers and scholars of criminal law have applied an analytical method to examine the elements of crime, and such elements are comprised of subjective elements (mens rea) and objective elements (actus reus). According to this, a crime is either an act or omission with a psychological bond relating to the physical act of the criminal. Regarding the crime of genocide, its elements are derived from the definition of genocide under the Genocide Convention and the Rome Statute. The Genocide Convention defines genocide as the commission of an act with the intent to destroy, either wholly or partly, a national, racial, ethnical, or religious group. However, the ‘genocidal intent’ or mental element to commit the crime of genocide was not considered in the military trials of Nuremberg and Tokyo. This ‘genocidal intent’ received its very first attention during the trials of two ad hoc international tribunals for the Former Yugoslavia and Rwanda. This paper attempts to discuss the definition of genocide under the Genocide Convention and the Rome Statute. This paper, then, focuses on the mental element of genocide and the approach of the international criminal courts during the trial of genocide. Abstrak Banyak ahli hukum pidana dan sarjana hukum pidana telah menerapkan metode analisis untuk mengkaji unsur-unsur kejahatan dan unsur-unsur tersebut terdiri dari unsur subyektif (mens rea) dan unsur obyektif (actus reus). Menurut ini, kejahatan adalah perbuatan atau kelalaian dengan ikatan psikologis yang berkaitan dengan perbuatan fisik pelaku kejahatan. Mengenai kejahatan genosida, unsur-unsurnya diturunkan dari pengertian genosida di bawah Konvensi Genosida dan Statuta Roma. Konvensi Genosida mendefinisikan genosida sebagai tindakan yang bertujuan untuk menghancurkan baik seluruhnya atau sebagian, kelompok bangsa, ras, etnis atau agama. Namun, ‘niat genosida’ atau unsur mental untuk melakukan kejahatan genosida tidak dipertimbangkan dalam pengadilan militer di Nuremberg dan Tokyo. ‘Niat genosida’ ini mendapat perhatian pertama selama persidangan dua pengadilan internasional ad hoc untuk Bekas Yugoslavia dan Rwanda. Tulisan ini mencoba untuk membahas definisi genosida di bawah Konvensi Genosida dan Statuta Roma. Artikel tersebut kemudian berfokus pada unsur mental genosida dan pendekatan pengadilan pidana internasional selama persidangan genosida. Kata kunci: niat genosida, konvensi genosida, kelompok tertentu, hukum pidana internasional, penghancuran